THE INFLUENCE OF MANPOWER AND HUMAN DEVELOPMENT INDEX ON ECONOMIC GROWTH IN DISTRICTS OF ACEH PROVINCE - Murtala Murtala; Irma Sapitri (Journal of Malikussaleh Public Economics, 2023)
This study aims to determine the effect of the workforce and the human development index (IPM) on economic growth in the districts of Aceh province in 2000-2020. This research uses multiple linear data for 20 years. This study used the Autoregressive Distributed Lag (ARDL) test analysis method. The results of this study indicate that in the long term and short term labor has a negative and insignificant effect on economic growth. Meanwhile, HDI in the long and short term has a positive and significant effect on economic growth.